PENDIDIKAN KESEHATAN MENINGKATKAN KEMAMPUAN MELAKUKAN PIJAT BAYI - Ferianto; Mawarti, Retno (MEDIA ILMU KESEHATAN, 2012)
Background: Baby massage is a massage performed with smooth palpation on the surface of a baby's skin, which aims to produce effects on nerves, muscles, respiratory system and blood circulation and lymph. When doing a preliminary study in Trimurti Village of Srandakan sub District, Bantul District, many parents of babies still did not know the benefits of baby massage and did not understand how to apply the correct massage independently. Objektive: The aim of this research is to determine the effect of health education about baby massage on the maternal behavior to massage her baby in Trimurti Village of Srandakan, Bantul, Yogyakarta 2011. Method: This was a quasi experimental study with a one group pretest-posttest study design. The study site was in Trimurti Village of Srandakan Bantul, Yogyakarta done in 2011. The sampling technique used purposive sampling with 32 respondents. Data analysis technique used McNemar Test with standard error (?) 0.05. Results: Maternal behavior to baby massage at the time of pretest was in majority not suitable with the technique with a score < 65 in 32 respondents, while the maternal behavior to baby massage at the time of posttest was in majority suitable with the technique with a score > 65 in 32 respondents. It was proven with McNemar Test showing the p-value = 0.000 (p<0.05). Conclusion: Health education about baby massage can increase on the maternal behavior in Trimurti Village, Srandakan, Bantul, Yogyakarta 2011.Mothers should broaden their insights about baby massage to enhance maternal behavior in applying baby massage techniques correctly to increase the baby’s growth and development. Keywords: Health education, Baby Massage, Bahavior